The paradox of weak ties in 55 countries. - Gee, Laura Katherine.; Jones, Jason J.; Burke, Moira.; Fariss, Christopher J.; Fowler, James H., 1970- (Tufts University. Tisch Library., 2017)
People find jobs through their social networks using ties of different strengths. Intuitively weak ties might be less useful because people communicate less often with them, or more useful because they provide novel information. Granovetter's early work showed that more job-seekers get help via acquaintances than friends (Granovetter, 1973) However, recent work on job-finding (Gee et al., 2017) shows an apparent paradox of weak ties in the United States: most people are helped through one of their numerous weak ties, but a single stronger tie is significantly more valuable at the margin. Although some studies have addressed the importance of weak ties in job finding within specific countries, this is the first paper to use a single dataset and methodology to compare the importance of weak ties across countries. Here, we use de-identified data from almost 17 million social ties in 55 countries to document the widespread existence of this paradox of weak ties across many societies. More people get jobs where their weak ties work. However, this is not because weak ties are more helpful than strong ties - it is because they are more numerous. In every country, the likelihood of going to work where an individual friend works is increasing - not decreasing - with tie strength. Yet, there is substantial variation in the added value of a strong tie at the margin across these countries. We show that the level of income inequality in a country is positively correlated with the added value of a strong tie, so that individual strong ties matter more when there is greater income inequality.